STRESS LEVEL AND SELF RELATION IN UNIVERSITY STUDENTS AND COACHES - İmamoğlu, Osman; Tutkun, Erkut; Sen, Gunay (Acta Scientiae et Intellectus, 2024)
In this study, the relationship between the stress level and self-concept of the university students and coaches was investigated. To 310 students and 90 coaches, stress level scale and self-design inventory were applied. The comparisons were made by student t test. There was a statistical difference between stress level and self-design scores according to age level of students and coaches (p<0,001), there was no significant difference according to height and body weight (p<0,001). As the age level increases, the stress score decreases. There were no significant differences in the self-concept score while the male had higher stress score than the female (p<0,001). It was found statistically significant that the coaches had higher stress scores than students (p<0,001). Coaches were found to have a more stressful and negative self-concept than students. Stress level of coaches should be lowered to improve their positive self-esteem.